A FOREWORD BY THE GUEST EDITORS: PROFESSOR ANNE BOOTH, EMINENT AND PROLIFIC SCHOLAR, GENEROUS FRIEND AND COLLEAGUE - J. Thomas Linbald; Thee Kian Wie (Masyarakat Indonesia, 2013)
This Festschrift in honour of Professor Anne Booth on the occasion of herimpending retirement from the Department of Economics at the School ofOriental and African Studies (SOAS), University of London, is to celebrateAnnes formidable scholarly achievements and her generosity in sharing herresearch findings with her many colleagues, friends, and students.